EGFR targeted therapies in lung cancer - Janne, Pasi (Henry Stewart Talks, 2009)
Lung cancer: facts and figures, Lung cancer survival, Lung cancer burden, EGFR targeted therapeutics, EGFR mutations, Why Do EGFR inhibitors work so well in EGFR mutant cancers?, Are EGFR TKIs better than chemotherapy?, Emergence of resistance to EGFR TKIs, Mechanisms of Gefitinib/Erlotinib resistance, EGFR signaling in EGFR mutant NSCLC, Analogous kinase mutations associated with drug resistance, Irreversible EGFR inhibitors, Clinical resistance is heterogeneous, Therapeutic targeting of other oncogenes in lung cancer, Incorporating genomics into treatment
Archived at 2018/05/31